2012
DOI: 10.1007/s10897-011-9477-3
|View full text |Cite
|
Sign up to set email alerts
|

Perception of Direct‐To‐Consumer Genetic Testing and Direct‐To‐Consumer Advertising of Genetic Tests among Members of a Large Managed Care Organization

Abstract: This small qualitative study was designed to determine possible attitudes toward and understanding of direct-to-consumer (DTC) genetic testing among members of a large managed care organization, and whether differences might exist between population groups. Ten focus groups were conducted by population type (high risk, White, African American, Hispanic/Latino) to determine knowledge, attitudes and beliefs about DTC genetics. Focus group transcripts were coded for attitudes toward and framing of the issue. Stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
15
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 56 publications
1
15
0
Order By: Relevance
“…In this study, the personal willingness to participate in genetic studies as expressed by the individuals we queried was based largely on personal or family benefits in addition to societal altruism. This finding is consistent with other studies that show participation in genetic research including biobanks,[11] direct to consumer personal genome testing [12, 13] and disease/condition[14] specific studies is motivated by individual, family and altruistic reasons. [15] In addition to societal benefits, researchers may need to especially consider and accurately frame the anticipated benefits of genetic research for individual or family members when enrolling African-American children.…”
Section: Discussionsupporting
confidence: 91%
“…In this study, the personal willingness to participate in genetic studies as expressed by the individuals we queried was based largely on personal or family benefits in addition to societal altruism. This finding is consistent with other studies that show participation in genetic research including biobanks,[11] direct to consumer personal genome testing [12, 13] and disease/condition[14] specific studies is motivated by individual, family and altruistic reasons. [15] In addition to societal benefits, researchers may need to especially consider and accurately frame the anticipated benefits of genetic research for individual or family members when enrolling African-American children.…”
Section: Discussionsupporting
confidence: 91%
“…Some participants highlighted the potential for test results to be overwhelming and emotionally taxing for themselves and their families, which reflects similar concerns that have been raised in the literature on commercial genomic testing and whole-genome sequencing for research purposes [20,22,26]. However, insights from research involving Alzheimer's disease patients and their families has shown that knowing one's genetic susceptibility for Alzheimer's disease allows individuals to plan for their futures [27] and that even in the face of receiving difficult information about one's disease risks, individuals exhibit emotional resilience [28,29].…”
Section: Discussionmentioning
confidence: 86%
“…However, one unique aspect of this study is that while this group of participants saw this type of testing as being useful for generating risk susceptibility information, they characterized the diagnostic potential for genomic testing as more valuable than predictive information about disease risks. This is a departure from the literature which has assessed prospective and actual user perspectives on commercial genomic testing platforms [11,12,22] and participants in personalized genomic research [23]. Participants in this study were especially enthusiastic about the potential for clinical genomic testing to help end a “diagnostic odyssey” and about its potential applications for children.…”
Section: Discussionmentioning
confidence: 99%
“…Those that did mentioned confidentiality and privacy concerns and fear of knowing, which have been noted elsewhere (Bloss et al 2010a;Goldsmith et al 2012;Hahn et al 2010;McGuire et al 2009;Rahm et al 2012;Wasson et al 2012). These concerns were limited and not weighty enough to preclude them from undergoing DTCGT and/or their concern to be informed was a higher priority.…”
Section: Discussionmentioning
confidence: 90%